2022
DOI: 10.1113/ep090151
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and blood pressure are similar in naturally menstruating and oral contraceptive pill‐using women during the higher hormone phases

Abstract: New Findings What is the central question of this study?Are there differences in blood pressure, arterial stiffness and indices of pressure waveforms between young oral contraceptive pill‐using and naturally menstruating women during lower and higher hormone phases of their cycles? What is the main finding and its importance?Blood pressure, arterial stiffness and indices of pressure waveforms are influenced similarly by exogenous and endogenous hormones. However, lower levels of exogenous hormones moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Our data extend these findings and show no differences in central blood pressure between pill days. Moreover, and contrary to some previous research [ 37 ], we did not observe any differences in brachial or central blood pressure between oral contraceptive users and eumenorrheic women.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data extend these findings and show no differences in central blood pressure between pill days. Moreover, and contrary to some previous research [ 37 ], we did not observe any differences in brachial or central blood pressure between oral contraceptive users and eumenorrheic women.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we cannot rule out that we overlooked some relevant differences in skeletal muscle adaptations between PRO-HIIT and PLA-HIIT. Finally, we note that three participating women (PRO-HIIT, N = 1; PLA-HIIT, N = 2) were using contraceptive pills, which could potentially have an influence on blood pressure [ 65 ]. However, due to the very small number of women using contraceptive pills and the comparable distribution between both groups, we did not expect a meaningful impact on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Forty‐three young, healthy women who were NAT ( n = 21) or taking OCPs ( n = 22) participated in the study. Participants were pooled from previously published studies conducted at UMD (Eagan et al., 2022 , 2021 ) and MU (Jacob et al., 2021 , 2022 ) to test new hypotheses proposed herein. Participants had no history of cardiovascular disease or other diseases (pulmonary conditions, metabolic conditions, cancer or stroke) that might alter vascular function, were not taking medications apart from oral contraceptives (antibiotics, non‐steroidal anti‐inflammatory drugs and blood pressure medication).…”
Section: Methodsmentioning
confidence: 99%
“…Forty-three young, healthy women who were NAT (n = 21) or taking OCPs (n = 22) participated in the study. Participants were pooled from previously published studies conducted at UMD (Eagan et al, 2021(Eagan et al, , 2022 and MU (Jacob et al, 2021(Jacob et al, , 2022 menstrual cycles (Munro et al, 2018) or regular and consistent use of the same brand and formulation of oral contraceptives for the last 6 months. All women also confirmed that they did not currently have an intra-uterine device or other hormonal implant.…”
Section: Participantsmentioning
confidence: 99%